PERLADANGAN TRADISIONAL KELOMPOK MASYARAKAT MONE DI MUNA SULAWESI TENGGARA - La Ode Topo Jers (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
This study discusses about the system and traditional cultivation model of Mone community at Muna District which is one of the most remote local communities. Traditional cultivation for Mone community groups as an effort to meet economic needs by utilizing natural resource is as a one of the survival choices. This research uses qualitative approach with a method and an ethnography analysis. The finding of the research shows that their local wisdom values ​​become the guidance in managing nature well, which is supported by adherence to customary and cultural rules inherited by ancestors from generation to generation. Moreover, the way of cultivation at Mone community can be interpreted as a social process which is seen as the unity of social-cultural in upholding and maintaining customs (norms) inherited by their ancestors. The way of Mone Community cultivaton as a backward community, can be used as a reference to understand the concept of balance in interacting. This concept is assumed that to improve the life for remote communities should not forget the approach of local wisdom. Each ethnic group has a local wisdom that built based on tradition and has been maintained for many years in preventing the flow of capitalist economic change or global wisdom.